1972
DOI: 10.1136/bmj.2.5816.729
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Surgery and Prolonged Spironolactone Therapy in Patients with Hypertension, Aldosterone Excess, and Low Plasma Renin

Abstract: SummaryThe effect of prolonged preoperative treatment with spironolactone has been studied in a series of 67 patients with hypertension, aldosterone excess, and low plasma renin. In the series as a whole a highly significant reduction in both systolic and diastolic pressures was achieved, with no evidence of escape from control during therapy lasting several years in some cases. The drug was equally effective in controlling blood pressure in patients with and without adrenocortical adenomata. Occasional unresp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
1
1

Year Published

1973
1973
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(48 citation statements)
references
References 40 publications
(44 reference statements)
3
43
1
1
Order By: Relevance
“…The endocrine effects seemed related to the dose, as previously reported. 40 - 41 However, only two patients were withdrawn from this study due to side effects.…”
Section: Discussionmentioning
confidence: 99%
“…The endocrine effects seemed related to the dose, as previously reported. 40 - 41 However, only two patients were withdrawn from this study due to side effects.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11] Small uncontrolled studies have also demonstrated its effectiveness in patients with resistant hypertension. [12][13][14][15] This is reflected in the latest British Hypertension Society guidelines, which recommend spironolactone as fourth-line therapy when other drugs have failed to control BP.…”
mentioning
confidence: 99%
“…The predictive value of spironolactone in indicating the likely hypotensive effect of adrenal surgery was emphasized by Brown et al 2 In that study, however, the drug was equally effective in controlling arterial pressure in patients with and without adenomas, although in the latter, arterial pressure rarely responds favorably to adrenal surgery. In a similar study" we showed that any measure reducing plasma volume in patients with primary aldosteronism (whether by sodium deprivation or combining hydrochlorothiazide with small doses of spironolactone) resulted in normalization of arterial pressure.…”
Section: -211mentioning
confidence: 96%